METALS BIOCONCENTRATION OF FRESHWATER FISHES IN CENTRAL KALIMANTAN AS AN EVALUATION CRITERIA FOR MANAGEMENT OF INLAND WATER FISHERY RESERVE - Dede Irving Hartoto; Awalina Awalina (BERITA BIOLOGI, 2000)
Heavy metal bioconcentration was examined and evaluated in the muscle of several of freshwater fishes species collected from a complex of some oxbow lakes in Kahayan River and from Lake Sembuluh, Central Kalimantan. The objective of the study was to find natural background values of heavy metals in water, sediment and its biomultiplication factor related to their concentration in water and the fish position in the foodweb. In this analysis,one to twenty-five grams of fish muscle samples was obtained from the posterior part of pectoral but anterior to anal fins. Water samples, which were taken from surface and bottom layers of the lakes, were mix and preserved with nitric acid. Sediment samples were obtained by using Ekman Grab and the interstitial waters were extracted by using wet digestion technique.Iron concentration in fish muscle is the highest in omnivorous, followed by that of in carnivorous and detritivorous fish. Manganese, lead and mercury had different pattern of bioconcentration levels. Bioaccumulation factor for each metal and at each food habit category was also variable; the lowest value of 0.7 for iron in second consumer and 28.2 for mercury in primary consumer. Mechanism of heavy metal intrusion to fish muscle is very intricate and apparently depends upon feeding habit of each species. Concentration of mercury in water and fish muscle was far above minimum risk level, but concentrations of iron, manganese and lead in water and fish was considered still safe for environment as well as for human health. Potential utilization of these results as evaluation criteria for fishery reserve is discussed.